Developing preclinical models for intervertebral disc degeneration: analyzing mechanical, molecular, and immunological interventions - Bonilla, Andres, author; Easley, Jeremiah, advisor; Dow, Steve, committee member; Puttlitz, Christian, committee member; Johnstone, Brian, committee member (Colorado State University. Libraries, 2024)
Low back pain is a prevalent global health issue, significantly affecting quality of life and contributing to economic burdens through reduced productivity and healthcare costs. Intervertebral disc degeneration (IVDD) is recognized as a major underlying cause of chronic low back pain. Despite advances in therapeutic strategies for IVDD, the translation of these treatments from preclinical research to clinical application remains challenging due to the lack of appropriate animal models that accurately mimic the complex pathophysiology of human IVDD. This document aims to address these limitations by developing and validating novel ovine and immune-induced animal models of IVDD, and to provide insights into the molecular, biomechanical, and immunological aspects of the disease. Chapter 1 introduces the clinical significance of low back pain and the central role of IVDD in its development. The chapter highlights the unmet need for robust preclinical models to facilitate the evaluation of potential therapeutic interventions. Chapter 2 reviews the existing literature on ovine models of IVDD, emphasizing their relevance to human spinal disorders due to the anatomical, physiological, and histological similarities between sheep and humans. Ovine models are particularly valuable for studying both spontaneous and induced IVDD, providing a critical platform for translational research. Chapter 3 presents a groundbreaking study that conducts the first comparative analysis of surgical, imaging, histological, and proteomic characteristics between cervical and lumbar intervertebral discs (IVDs) in an ovine model of IVDD. The results demonstrate a comparable progression of IVDD in both regions, challenging the longstanding emphasis on lumbar IVDs in research and underscoring the importance of cervical models in advancing our understanding of the disease. These findings have substantial clinical and research implications, indicating that treatments traditionally developed and evaluated for lumbar IVDD may also be relevant for cervical pathology. Furthermore, the identification of specific biomarkers, could significantly enhance early diagnosis and inform the development of tailored therapeutic interventions. Chapter 4 introduces a novel model utilizing extracorporeal shock wave therapy (ESWT) applied to ovine IVDs. While no significant evidence of IVDD was observed during the 12-week study period, localized bone formation at the treatment sites was identified. This finding provides important insight into the effects of ESWT, suggesting that while it is conventionally used as a therapeutic modality, it may also have unintended consequences, such as promoting bone formation, which could potentially lead to tissue damage. These results highlight the need for further refinement of shock parameters to reliably induce progressive IVDD, offering valuable data for future research into both the therapeutic and adverse effects of ESWT in spinal treatments. In Chapter 5, a mechanical compression model utilizing MRI-compatible materials was developed to induce disc degeneration in ovine lumbar discs, marking the first report of its kind to our knowledge. This innovation allows for the longitudinal tracking of degeneration with a measurable rate of compression, leveraging MRI as the most critical tool for diagnosing IVDD. While the model successfully induced biomechanical changes, including reduced disc height and altered neutral zone dynamics, no significant histological or biochemical degeneration was observed. However, these findings provide valuable insights for future researchers using mechanically induced models, offering a foundation to refine and optimize the model for tracking the progression of degeneration more accurately. Chapter 6 explores the role of immune system in IVDD by developing an immune-induced model using a nucleus pulposus (NP) antigen vaccine. Rabbits were vaccinated against NP following IVD injury, leading to accelerated degeneration in comparison to non-vaccinated animals. This study highlights the potential of immune responses in accelerating disc degeneration, offering a novel avenue for understanding the interplay between immunity and IVDD progression. This document contributes to the advancement of IVDD research by establishing and validating novel animal models, including ovine, mechanical compression, and immune-induced models. The proteomic findings and biomechanical evaluations presented in this document offer critical insights into the molecular pathways involved in IVDD and lay the foundation for the development of customized therapeutic strategies. Future research should focus on refining these models to better replicate the complexities of human IVDD and explore long-term therapeutic interventions that can mitigate degeneration and restore disc function.
Keywords: disc; spine; intervertebral disc; animal models